Is there sufficient evidence to support the health benefits of including donkey milk in the diet? - Khan, Muhammad Zahoor; Chen, Wenting; Li, Mengmeng; Ren, Wei; Huang, Bingjian; Kou, Xiyan; Ullah, Qudrat; Wei, Lin; Wang, Tongtong; Khan, Adnan; Zhang, Zhenwei; Li, Liangliang; et al. (Frontiers in Nutrition, 2024)
Donkey milk has attracted attention due to its distinctive nutritional composition and potential health advantages, particularly because of its whey protein content, which includes lysozyme, α-lactalbumin, lactoferrin, and β-lactoglobulin and vitamin C, among other components. These elements contribute to immunoregulatory, antimicrobial, antioxidant, and anti-inflammatory properties, positioning donkey milk as a possible therapeutic option. In addition, due to the low levels of caseins, the casein-to-whey protein ratio, and the β-lactoglobulin content in donkey milk, it presents an optimal alternative for infant formula for individuals with cow's milk allergies. Moreover, research into donkey milk's potential for cancer prevention, diabetes management, and as a treatment for various diseases is ongoing, thanks to its bioactive peptides and components. Nevertheless, challenges such as its low production yield and the not fully understood mechanisms behind its potential therapeutic role necessitate more thorough investigation. This review consolidates the existing knowledge on the therapeutic possibilities of donkey milk, emphasizing its importance for human health and the need for more detailed studies to confirm its health benefits.